Unveiling the anti-tumor and anti-fibrotic potentials of Kanglaite in esophageal cancer through PVT1/TGF-β/Smad axis inhibition - Li, Xiuqing; Bian, Ka; Zhang, Ji; Luo, Kaili; Dong, Tao; Luo, Chenglin (Italian Journal of Food Science, 2024)
Esophageal cancer (EC) poses a significant challenge among tract tumors worldwide due to its complex molecular composition, which remains largely unexplored. Kanglaite (KLT), a medicine known for its anti-tumor properties, is emerging as a potential ally in the culinary world. Plasmacytoma Variant translocation 1 (PVT1) plays a significant role in the complex nature of esophageal cancer, showing high expression levels in tumor tissues. During our investigation, we discovered a higher presence of PVT1 in cancer tissues, which led us to explore its functions further. Through manipulating techniques, we found that inhibiting PVT1 not only hinders the growth of esophageal cancer cells but also reduces fibrosis. This is similar to enhancing the texture and flavor of a dish. Our study reveals the interactions at play, highlighting how PVT1 orchestrates the TGF β/Smad pathway – a component in the development of esophageal cancer. Introducing KLT, an expert poised to revolutinize the approach to cancer treatment. Our research demonstrates KLT’s effectiveness in regulating the PVT1/TGF-β/Smad axis, uncovering its fibrotic properties, and its ability to hinder the progression of esophageal cancer. With these discoveries, KLT emerges as a promising option for the treatment of esophageal cancer.